The Internalization Entrepreneurship Values of Students at Al Fahham Islamic Boarding School Purworejo - Ashif Az Zafi; Maisyanah Maisyanah (LP2M IAIN kUDUS, 2023)
This study aimed to explain the process of internalization of entrepreneurship values to students, to identify the entrepreneurship values of students, and to explain the output produced from establishing the entrepreneurial value of students at the Al Fahham Islamic Boarding School. This study was qualitative research that used interviews, observation, and documentation to collect the data. The respondents in this study were cottage caretakers, 2 administrators, and 8 students. Data collected were analyzed through the process of data reduction with select methods related to the goal of this research. Then, the result of data reduction was presented in a systematic, easy so this could be understood easily with a draft or theory. Furthermore, the data could be concluded based on the goal of this research. This study describes data about the internalization process using the planning, acting, and evaluation theory. The values of santri entrepreneurs are explained by the concept of indicators of entrepreneurial attitudes. Meanwhile, taxonomic concepts are used in the form of cognitive, affective, and psychomotor to explain the output or results. This study concluded that to realize students with entrepreneurial attitudes, the students needed to determine goals, programs, and proper evaluation methods. Al- Fahham Islamic boarding school’s goal was to create an entrepreneurial spirit in the students themselves and to create capable and skilled cadres of students who serve the community. Implemented programs supported objective boarding schools, forming the Islamic Boarding School Business Unit (entrepreneurship) and giving spiritual motivation (spiritual). The evaluation was done at the Islamic boarding schools Al Fahham to create students’ entrepreneurial spirit through monthly income reports and appreciation with the method of giving gifts (rewards) to successful students who reach beyond target income. Internalization process of entrepreneurship values to the students successfully grows up entrepreneur attitude such as discipline, sincerity, independence, hard work, religion, togetherness, caring, affection, simplicity, respect, courtesy, responsibility, and honesty. This value proved that it could help the pesantren alumni to have some skills needed by entrepreneurs, such as creative thinking skills, skills in making decisions to be independent, and leadership skills.